2021
DOI: 10.1002/lary.29363
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Subglottic Stenosis Using Ultrashort Echo Time MRI in a Rabbit Model

Abstract: Objective/Hypothesis: To assess the ability of ultra-short echo time (UTE)-MRI to detect subglottic stenosis (SGS) and evaluate response to balloon dilation. To correlate measurements from UTE-MRI with endotracheal-tube (ETT)-sizing and to investigate whether SGS causes change in airway dynamics.Study Design: Animal research study. Methods: Eight adult New-Zealand white rabbits were used as they approximate neonatal airway-size. The airways were measured using ETT-sizing and 3D UTE-MRI at baseline, 2 weeks pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Magnetic resonance imaging has been used to noninvasively investigate airway abnormalities such as tracheobronchomalacia and subglottic stenosis in neonates and animal models of neonates [101][102][103]. Retrospective respiratory gating of UTE MRI, the same sequence that evaluates the lung parenchyma, simultaneously allows measurement of 3-D dynamic changes in lumen size [74].…”
Section: Central Airway Magnetic Resonance Imagingmentioning
confidence: 99%
“…Magnetic resonance imaging has been used to noninvasively investigate airway abnormalities such as tracheobronchomalacia and subglottic stenosis in neonates and animal models of neonates [101][102][103]. Retrospective respiratory gating of UTE MRI, the same sequence that evaluates the lung parenchyma, simultaneously allows measurement of 3-D dynamic changes in lumen size [74].…”
Section: Central Airway Magnetic Resonance Imagingmentioning
confidence: 99%
“…Non-invasive methods that utilize radiographic studies, including computed tomography and magnetic resonance imaging, have been demonstrated accuracy in detection and quantification of subglottic stenosis. [11][12][13] 3D airway reconstructions of the airway based on endoscopic video evaluation have been shown to be reliable strategies in both phantom airway modeling, as well as ex-vivo animal experiments. [14][15][16] However, these processes can be time consuming, may subject patients to ionizing radiation, and do not provide intraoperative feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the standard method of evaluating subglottic stenosis described by Myer et.al 4 is limited by its single dimensionality; it does not provide other important information, such as the location or length of stenosis. Non‐invasive methods that utilize radiographic studies, including computed tomography and magnetic resonance imaging, have been demonstrated accuracy in detection and quantification of subglottic stenosis 11–13 . 3D airway reconstructions of the airway based on endoscopic video evaluation have been shown to be reliable strategies in both phantom airway modeling, as well as ex‐vivo animal experiments 14–16 .…”
Section: Discussionmentioning
confidence: 99%